The role of Guanxi in fostering adaptability and work engagement among educators in international educational institutions - Li, Shuang; Yu, Shougang (Frontiers in Psychology, 2024)
The present study delves into the intricate relationships between individual adaptability, various dimensions of Guanxi-Ganqing, Renqing, and Xinren-and work engagement among educators working in international educational institutions across major cities in China. Guanxi refers to complex system of social networks and influential relationships that facilitate business and other dealings. Ganqing, Renqing, and Xinren represents distinct but interconnected dimensions. Ganqing refers to the emotional bonding or personal affection that is developed within a Guanxi relationship. Renqing can be understood as the norm of reciprocity or the social obligation to respond to another's needs and to maintain the balance of give and take in relationships. Finally, Xinren: This dimension represents trust and credibility in Guanxi relationships. Employing online data collection via the Qualtrics platform, the study investigates the impact of individual adaptability on work engagement, particularly examining the mediating roles of different Guanxi dimensions. Utilizing Hayes' Process model 80 for mediation analysis, our findings demonstrate a statistically significant direct effect of individual adaptability on work engagement, thus supporting Hypothesis 1 (H1). The analysis reveals that this relationship is partially mediated by other variables within our model.Significantly, the study highlights the nuanced roles of the Guanxi dimensions of Ganqing, Renqing, and Xinren in this context. This mediated chain model suggests a more complex interaction between these factors than previously understood.Our analysis also reveals the differential impacts of these Guanxi dimensions. Notably, Ganqing exhibited a greater influence on work engagement compared to Renqing and Xinren. This finding underscores the critical role of affective bonds in social ties and their importance in enhancing work engagement. These results are detailed in our results section and illustrated in Figure 3. The study contributes to the understanding of how individual adaptability and various Guanxi dimensions interact to influence work engagement, offering valuable insights for both academic research and practical application in organizational settings. These findings are contextualized within Confucian values and the ongoing internationalization of education. The study thus advances the theoretical discourse while offering practical recommendations for educators and institutional policies. Limitations and future research directions are also elaborated.